Markups and market structure in South Africa: What can be learnt from new administrative data? - Joshua Budlender (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
The South African economy is generally understood to be characterised by high levels of product market concentration and high firm markups. This paper reviews the existing literature and discusses what can be learnt from new administrative firm-level panel data. I present new evidence on South African markups, industrial concentration, and the firm-size distribution, for sectors across the South African economy. I find that conclusions on whether markups are 'high' or 'low' are heavily dependent on the method used, and I show that this is consistent with the prior literature. There is however preliminary evidence that markups have generally declined over the 2010-14 period. I argue that it is difficult to make strong conclusions about industrial concentration using cross-industry study, and that high and growing concentration across the South African economy is yet to be conclusively shown. I also investigate how firm-level markups are related to industry-level concentration and firm-level market share. While some patterns emerge, I argue that their economic meaning is unclear.
Keywords: L11; D22; C81; 330; markups; market power; concentration; firm-size distribution; South Africa